The security implications of using feminist methodologies to study gender-based violence in Yemen - Al-Refaei, Sawsan (Frontiers in Research Metrics and Analytics, 2024)
IntroductionThis paper examines the political and security implications of gender-based violence (GBV) research in Yemen during the period (2019–2023). As various radical groups are gaining power over Yemeni land, radical views toward women and gender equity and equality shape the experiences of GBV survivors, practitioners, and researchers in the North of Yemen. Policing Houthi ideologies in Yemen have curtailed GBV research and subjected feminist research to myriad risks. If this situation continues, experiences of women and girls in Yemen will not be captured by research. Their stories and needs will not be captured by humanitarian and peace-building actors.MethodologyFindings of this study are based on primary data from key informant interviews with 25 GBV researchers actively engaged in Yemen. Sampling followed the snowballing technique.ResultsThe findings examine political and security power dynamics after the Houthi radical group took control in the north of Yemen, and implications on GBV research design. Anti-feminist ideologies coupled with extreme security measures have impacted quality of GBV study methodologies as well as researchers' safety and mobility. Donors of previously established GBV programs and research were harassed to change research topics or lose permission to speak to local communities or collect data from aid beneficiaries. Researchers who do not follow new rules of engagement with the community are detained, harassed and their devices and databases are confiscated. Terms like “gender” and “GBV” are not deemed acceptable as these are western concepts that do not align with new community values. The findings highlight the need to use conflict-sensitivity and Do No Harm principles in settings where GBV work is scrutinized. It also challenges the orthodox definition of “GBV evidence” and explores the ethical implications of the use of alternative means to collecting data. Findings also provide insight into valuable alternative methodologies that allow local and national researchers to continue studying GBV in conflict impacted areas without exposing themselves to actual or perceived risk. The paper proposes concrete approaches that can mitigate political and security risk on both researchers and GBV survivors.